Treatment with either obestatin or ghrelin attenuates mesenteric ischemia-reperfusion-induced oxidative injury of the ileum and the remote organ lung - YEGEN, BERRAK; ERCAN, FERİHA; YÜKSEL, MERAL; AKKİPRİK, MUSTAFA; ÖZER, SIDIKA AYŞE (ELSEVIER SCIENCE INC, 2015)
To evaluate the effects of exogenous ghrelin or obestatin on intestinal injury and accompanying pulmonary injury, intestinal ischemia-reperfusion (I/R) was induced in rats by obstructing the superior mesenteric artery for 60 min, whereas laparotomy was performed in the sham group. At the beginning of the 90-min reperfusion period, the rats were injected with obestatin (100 mu g/kg), ghrelin (10 ng/kg), or saline intravenously (iv). At the end of reperfusion, the blood, ileum, and lung samples were taken for the histological and biochemical assays. In the saline-treated I/R group, the increased serum interleukin (IL)-1 beta level, high damage scores, and elevated tissue malondialdehyde level and collagen content in both tissues were significantly reduced by obestatin or ghrelin. Increased ileal myeloperoxidase activity of the saline-treated I/R group was reduced by treatment with obestatin or ghrelin, whereas increased pulmonary myeloperoxidase activity was reduced with administration of obestatin. Increased DNA fragmentation in the ileum of the saline-treated I/R group was reduced by both peptides. Elevated luminol-lucigenin chemiluminescence levels and nuclear factor kappa B (NF-kappa B) messenger RNA ( mRNA) expression in the ileum of the saline-treated-I/R group were significantly decreased by obestatin or ghrelin treatment. I/R-induced depletion of the antioxidant glutathione in both ileal and pulmonary tissues was prevented with either obestatin or ghrelin treatment. Administration of either obestatin or ghrelin exerts similar protective effects against I/R-induced ileal and pulmonary injury, thus warranting further investigation for their possible use against ischemic intestinal injury. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Ghrelin; Obestat in; Intestinal ischemia-reperfusion injury; Lung injury; Oxidant damage; FACTOR-KAPPA-B; INFLAMMATORY-BOWEL-DISEASE; HUMAN ENDOTHELIAL-CELLS; ISOLATED RAT-HEART; INTESTINAL ISCHEMIA/REPERFUSION; ISCHAEMIA/REPERFUSION INJURY; SIGNALING PATHWAY; MUCOSAL INJURY; FOOD-INTAKE; HORMONE